PENDEKATAN HERMENEUTIKA AMINA WADUD: GENDER DALAM KONSEP HUSBAND AND WIFE - Munirah Munirah; umi sumbulah umi (university Of islam, 2023)
Islam is a religion that highly upholds justice without discriminating between men and women. However, in line with the times, limitations and differences in understandingreligion have become a scourge that glorifies certain genders and demeans others. Inequality in social roles based on gender is still maintained under the pretext of religious doctrine. Religion is involved to preserve conditions in which women do not consider themselves equal to men. It is not impossible that behind this theological awareness there is anthropological manipulation aimed at establishing a patriarchal structure, which is generally detrimental to women and only benefits certain classes in society. Seeing this paradigm shift, Amina Wadud tries to boost understanding that has strayed far from the Al-Qur'an's respect for women.